Using Parallel Diesel Generator and Fuel Cell as an Islanded Microgrid - Navid Jalilvand (International Journal of Engineering and Management Research, 2020)
By improving technology for extracting higher produced power from Renewable Energy Resources (RES), and reducing CO2 emission, a new concept called Microgrid has been introduced in the electrical systems. The microgrid is an integration of loads and RES which can work independently and interconnected to the grid. In this paper, a microgrid with two different sources Diesel Generator and Fuel Cell is presented. Conventional droop control is responsible to deliver power to the load. The detailed design and simulated systems for Diesel Generator and Fuel Cell are given and extracting the droop controller is shown. The effectiveness of the presented system is validated in the MATLAB/Simulink environment.